THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP STYLE AND ORGANIZATIONAL LEARNING: THE MEDIATING EFFECT OF THE ORGANIZATIONAL CAREER GROWTH OF THE ACADEMICS OF THE UNIVERSITY OF DJIBOUTI - Khairuddin, Sheikh Muhamad Hizam Sheikh; Omar, Mouktar Ahmed; Hasim, Muhammad Asyraf (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to increase the quality of education provided by the academics of the University of Djibouti. The study suggests that this objective can be achieved through the relationship between transformational style, organizational career growth, and organizational learning of academics of the University of Djibouti. Transformational leadership theory was conceptualized using Bass (1985) model, affective commitment developed by Allen and Mayer (1991), and organizational learning developed by Huber (1991). The sample of the study consists of 198 out of 255 of total population of the academics of the University of Djibouti. A quantitative approach was deployed in the study. The data was analyzed through descriptive and inferential statistics. In testing hypothesis correlation, multiple and hierarchical regressions were applied. The result of the survey revealed that transformational leadership style and organizational learning are significant and positively related, and that transformational leadership style is related to organizational career growth significantly as well. Moreover, the results showed that organizational career growth partially mediates the relationship between transformational leadership style and organizational learning. Based on the result of the study, it is recommended the establishment of transformational leadership style as a means of developing the quality of the education of the University. Nevertheless, it was acknowledged that the implementation of organizational learning increases the accumulation of knowledge of the academics in sharing their knowledge. Furthermore, the addition of mediating effect of organizational career growth in the relationship between transformational leadership style and organizational learning would improve the quality of education in the University of Djibouti.